Structural models of forming an integrated information and educational system “quality management of higher and postgraduate education” - Biloshchytskyi, Andrii; Omirbayev, Serik; Mukhatayev, Aidos; Kuchanskyi, Oleksandr; Hlebena, Мyroslava; Andrashko, Yurii; Mussabayev, Nurken; Faizullin, Adil (Frontiers in Education, 2024)
The study examines the design of an information and educational System for quality education management. The requirements for the information environment of universities are formulated. The delineation of distinct stages in the technological process for shaping the values of information objects is outlined, achieved through the execution of information procedures. These procedures generate a technologically comprehensive product applicable within the university context. A set of heterogeneous systems for automating university activities makes obtaining integral characteristics based on information from different sources difficult. The research suggests an approach that allows you to get rid of the disadvantage. The introduction of an integrated information environment has been reviewed. To implement the information system "Quality Management of Higher and Postgraduate Education," a conceptual model of the system architecture and a logical structure was developed. The developed information model was based on the model of a complex information and educational environment of a higher educational institution and the Ontological model of the database of the integrated information and educational environment. The preliminary results of the pilot implementation of the system in the activities of Astana IT University are summarized, which made it possible to improve the quality management of the educational process.